2020
DOI: 10.1038/s41598-020-59876-6
|View full text |Cite
|
Sign up to set email alerts
|

Renal accumulation of prooxidant mineral elements and CKD in domestic cats

Abstract: felids have a high incidence of chronic kidney disease (cKD), for which the most common renal lesion is chronic interstitial nephritis (cin). cin can be induced by tissue oxidative stress, which is determined by the cellular balance of pro-and anti-oxidant metabolites. Fish-flavoured foods are more often fed to cats than dogs, and such foods tend to have higher arsenic content. Arsenic is a pro-oxidant metallic element. We propose that renal accumulation of pro-oxidant elements such as arsenic and depletion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 70 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…This could be related to the ratio of renal excretion since it is their main excretion route. In a recent study in dogs and cats with chronic interstitial nephritis was observed that the ratio of Mo excretion in urine was lower than in healthy animals [ 39 ]. In humans, it has been suggested that high serum Mo concentrations could contribute to dialysis-related bone disease in patients requiring long term hemodialysis, as massive Mo accumulation causes joint deformity and arthritis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could be related to the ratio of renal excretion since it is their main excretion route. In a recent study in dogs and cats with chronic interstitial nephritis was observed that the ratio of Mo excretion in urine was lower than in healthy animals [ 39 ]. In humans, it has been suggested that high serum Mo concentrations could contribute to dialysis-related bone disease in patients requiring long term hemodialysis, as massive Mo accumulation causes joint deformity and arthritis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Information on Mo concentrations in serum of renal patients is very scarce. A recent study in dogs and cats with chronic interstitial nephritis demonstrated that less Mo was excreted in urine than in healthy animals [44]. In humans, it has been suggested that high serum Mo concentrations may contribute to dialysis-related bone disease in patients requiring long term hemodialysis, as massive Mo accumulation causes joint deformity and arthritis [45].…”
Section: Discussionmentioning
confidence: 99%